[PS 01-11] BIOCHEMICAL PROPERTIES OF THE N-TERMINALLY PALMITOYLATED ADRENOMEDULLIN. (September 2016) - Tokashiki, Mariko; Kubo, Keishi; Kuwasako, Kenji; Nagata, Sayaka; Kato, Johji; Kitamura, Kazuo
Abstract : Objective: Adrenomedullin(AM) is a vasodilator peptide having pleiotropic effects including cardiovascular protection and angiogenesis. Because of these beneficial effects, AM appears to be a promising therapeutic tool for human diseases such as myocardial infarction or peripheral artery disease. However, intravenous injection of AM stimulates sympathetic nerve activity due to the short-acting potent vasodilation resulting in increased heart rate and renin secretion. To lessen those acute unfavorable actions, we conjugated the N-terminal palmitoylation human adrenomedullin, and examined biological of palmitoylation AM in the present study. Design and Method: N-termial synthesized human AM peptide was conjugated with palmitic acid, and then palmitoylation AM was obtained-by purification with HPLC. Biological effects in vitro stimulating intracellular cAMP, a major second messenger of AM, were examined using cultured human embryonic (HEK)-239 cells stably expressing a specific AM receptor. Blood pressure-lowering effects in vivo were tested by intravenous injections of palmitoylated AM or native AM peptides into anesthetized rats. Plasma disappearance curve of peptides were evaluated by the two compartment model. Results: Palmitoylated AM stimulated intracellular accumulation of cAMP in cultured HEK-293 cells, as did native human AM peptide, in a dose-dependent manner. pEC50 of palmitoylatted AM was lower than native AM (8.49 ± 0.12 vs. 9.17 ± 0.12mean ± SEM, P < 0.05), but no difference was noted in the maximum response of cAMP (579.9 ± 24.5 vs. 667.2 ± 24.5 pmol/well) . The first and second plasma half-lives of native AM were 0.0046 min and 13.36 min, while those of palmitoylated AM were 1.15 min and 599.03 min, respectively. Both half-lives of the palmitoylated peptide were significantly prolonged, as compared with the native peptide (P < 0.05). Conclusions: N-terminally palmitoylated AM stimulated cAMP production in vitro, showing smaller acute hypotensive action and a prolonged plasma half-life in comparison of native AM peptide in vivo. The present results suggest a possibility for palmitoylated AM as a therapeutic tool with lessened unfavorable effect of acute hyportensin of native AM.